Teologi Biblika Mazmur 150: Strategi Interkultural Pelayanan Pujian bagi Pertumbuhan Jemaat - Tomas Purnomo; Timotius Sukarna; Sri Rezeki (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2026)
This study aims to develop a strategy for developing praise and worship services through a deeper biblical theology of Psalm 150, as a fundamental solution for congregational growth at YHS Eka Sinta Church in Kapuas Regency. The main premise of this study is based on the crucial disconnect between contemporary church music practices, which tend to be performative, and the essence of the doxology authoritatively contained in the text Scripture. By integrating descriptive qualitative methods and an exegetical biblical theology approach, this study explores the imperative meaning and poetic structure of Psalm 150 and then engages them in intercultural dialogue with the sociocultural context of local churches in Kalimantan. The results reveal that the biblical theology Psalm 150 emphasizes the totality of instrumental use and the universality of the subject of praise as an absolute reflection of God's sovereignty and might. Field findings indicate that the effectiveness of music services is often hampered by technical limitations and theological shallowness of liturgical ministers. This study concludes that healthy congregational growth, both in terms of spiritual quality and quantity, is rooted in the extent to which the church able to actualize biblical theological values ​​in expressions of praise that are relevant and resonate with the cultural background and local identity of its congregation. The resulting strategy offers a holistic ministry model, in which church music returns to its essential function as an instrument of faith transformation and a means of growing the Kingdom of God, adaptively yet faithful to the biblical text.